A novel lead and lag compensator circuit employing a single current feedback operational amplifier. (November 2020) - Buzcu, Yusuf; Topaloglu, Serkan; Ayten, Umut Engin; Sagbas, Mehmet
Abstract: In this study, a novel lead and lag type compensator circuit is proposed using a single active component, namely, the current feedback operational amplifier (CFOA). The proposed circuit has only one CFOA, two grounded resistors and two grounded capacitors. The input impedance of the proposed compensator is designed to be high whereas the output impedance is low. In terms of input and output impedance values, the proposed topology is suitable for a cascade connection with the voltage-mode structure not requiring buffer circuits, both at the input and output of the circuit. Moreover, the proposed circuit offers the advantage of controlling the poles and zeros orthogonally. The non-ideal effects depending on the active component are also presented in the paper. The commercially available AD844 integrated circuit component was used as the CFOA component in the proposed lead and lag compensator circuit and circuit simulations were performed using PSpice. Moreover, the electrical performance of the circuit was demonstrated by experimental studies. The achieved theoretical, simulation and experimental results are given with a comparison. Finally, a closed-loop control system application was given using the proposed compensator circuit and the operation of the circuit was demonstrated with PSpice simulations.